Dancing on water [compact disc] : solo piano improvisations in A432 - Kater, Peter (Points of Light Records : Kater Music/ BMI, 2017)
The 12-time Grammy Award nominated pianist takes us on an intimate journey of connection, vulnerability and transformation. This musical pilgrimage is a discovery and expression of the unique radiant beauty and creative lightness of being that exists within each of us.